2016
DOI: 10.3109/13880209.2015.1107747
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of DMBA/croton oil induced mouse skin papilloma byApodytes dimidiatamediated by its antioxidant and antimutagenic potential

Abstract: Context Considering the role of cellular oxidative stress in mutations and subsequent transformation, phytochemicals with antioxidant potential has become a primary choice as chemopreventives. Apodytes dimidiata E. Mey. Ex. Arn (Icacinaceae), a widely used plant in Zulu traditional medicine, is reported to possess antioxidant activity. Objective To investigate the chemopreventive efficacy of methanol extract of A. dimidiata leaf (AMF). Materials and methods Antimutagenic potential of AMF (25, 50 and 75 mg/plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…It is likely that NO scavenging ability of AMF may have a contributory role in nephroprotectivity. In an earlier study, NaF-induced imbalance in redox status was found to be regained by AMF administration in mice (Divya et al 2016). Thus, the nitric oxide and other oxygen free radical scavenging phytoconstituents in AMF might be responsible for the nephroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that NO scavenging ability of AMF may have a contributory role in nephroprotectivity. In an earlier study, NaF-induced imbalance in redox status was found to be regained by AMF administration in mice (Divya et al 2016). Thus, the nitric oxide and other oxygen free radical scavenging phytoconstituents in AMF might be responsible for the nephroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical screening of leaf acetone extract showed the presence of saponins, tannins, terpenes, steroids and flavonoids (Masoko & Nxumalo 2013). Moreover, in our previous studies, the antitumour (Divya et al 2015) and chemopreventive (Divya et al 2016) effects of A. dimidiata were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The level of lipid peroxidation in the skin tissue was determined by measuring the MDA content using the method described by Divya et al 2016 16. Briefly, 0.2 ml of homogenate was mixed with 0.2 ml of sodium dodecyl sulphate (8.1%), 1.5 ml of acetic acid (pH 3.5, 30%) and 1.5 ml of thiobarbituric acid (0.8%).…”
Section: Methodsmentioning
confidence: 99%